Windows Server 2003 (Hacking Exposed) - Scambray Joel (MC Graw Hill, 2006)
"The most demystifying source of information since Toto exposed the Wizard. Hacking Exposed Windows Server 2003 eliminates the mystique and levels the playing field by revealing the science behind the curtain." --Greg Wood, General Manager, Information Security, Microsoft Corporation